Penyuluhan Stunting Pada Ibu Program Keluarga Harapan Dusun Karang Semanding, Desa Sukorejo, Kecamatan Bangsalsari, Kabupaten Jember - Ari Septianingtyas; Qory Zuniana; Tidar Aden Hawa; Endang Wahyu Pudjiastutik; Abdul Hadi; Ahmad Fauzi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2023)
In Indonesia, stunting is also an urgent public health problem. This study identified several main factors that contribute to stunting, such as family income, exclusive breastfeeding practices, parental education, nutritional knowledge, food access, and complementary feeding practices. Awareness and appropriate action from the community is very important in preventing stunting. The aim of the implementation activities in Karang Semanding Hamlet, Sukorejo Village, Bangsalsari District, Jember Regency is to overcome the problem of stunting by providing counseling and assistance to pregnant women and toddlers who are members of the Family Hope Program (PKH). The training was attended by 25 PKH members. The results of the activity showed that there was an increase in members' knowledge about stunting and stunting prevention, who initially did not understand, now they understood. It is hoped that future activities can apply stunting prevention methods to improve health and reduce stunting rates. Therefore, it is hoped that education and counseling about stunting will be key in efforts to overcome this problem and improve the quality of life for children in the future.